P‐Nitrophenylcarbonates: A New Class of Compounds for Chemodosimetric Colorimetric Fluoride Anion Sensing Detectable by the Naked Eye. Issue 5 (6th February 2019) - Yadav, Amit Kumar; Chilukuri, Harsha; Kumari, Linthoinganbi Raj; Karthikeyan, Muthukumarasamy; Fernandes, Moneesha
Abstract: A new class of compounds containing the p ‐nitrophenylcarbonate motif is reported, that can selectively sense fluoride anions over other halide anions with a detection limit ranging from 0.29 to 0.48 μM. The fluoride ion acts as nucleophile, leading to the liberation of p ‐nitrophenol, that is easily detectable and quantifiable colorimetrically. Abstract : p ‐Nitrophenylcarbonates are reported, to selectively sense fluoride anions over other halide anions, with a detection limit between 0.29 to 0.48 μM. The liberation of p ‐nitrophenol during the reaction with fluoride ions leads to the appearance of a yellow colour that is easily detectable by the naked eye.